2D FeOCl: A Highly In‐Plane Anisotropic Antiferromagnetic Semiconductor Synthesized via Temperature‐Oscillation Chemical Vapor Transport. Issue 14 (24th February 2022) - Zeng, Yi; Gu, Pingfan; Zhao, Zijing; Zhang, Biao; Lin, Zhongchong; Peng, Yuxuan; Li, Wei; Zhao, Wanting; Leng, Yuchen; Tan, Pingheng; Yang, Teng; Zhang, Zhidong; et al.
Abstract: 2D van der Waals (vdW) transition‐metal oxyhalides with low symmetry, novel magnetism, and good stability provide a versatile platform for conducting fundamental research and developing spintronics. Antiferromagnetic FeOCl has attracted significant interest owing to its unique semiconductor properties and relatively high Néel temperature. Herein, good‐quality centimeter‐scale FeOCl single crystals are controllably synthesized using the universal temperature‐oscillation chemical vapor transport (TO‐CVT) method. The crystal structure, bandgap, and anisotropic behavior of the 2D FeOCl are explored in detail. The absorption spectrum and electrical measurements reveal that 2D FeOCl is a semiconductor with an optical bandgap of ≈2.1 eV and a resistivity of ≈10 −1  Ω m at 295 K, and the bandgap increases with decreasing thickness. Strong in‐plane optical and electrical anisotropies are observed in 2D FeOCl flakes, and the maximum resistance anisotropic ratio reaches 2.66 at 295 K. Additionally, the lattice vibration modes are studied through temperature‐dependent Raman spectra and first‐principles density functional calculations. A significant decrease in the Raman frequencies below the Néel temperature is observed, which results from the strong spin−phonon coupling effect in 2D FeOCl. This study provides a high‐quality low‐symmetry vdW magnetic candidate for miniaturized spintronics. Abstract : Good‐quality centimeter‐scale antiferromagnetic semiconductor FeOCl single crystals are controllably synthesized by developing a temperature‐oscillation chemical vapor transport method. The semiconducting characteristics, strong in‐plane anisotropies, and spin−phonon coupling effect of the 2D FeOCl are explored in detail. This study provides a high‐quality low‐symmetry van der Waals magnetic candidate for miniaturized spintronic devices.